Dampak Hukum Hak Waris terhadap Perkawinan Beda Agama Antara Hindu dengan Islam Menurut Hukum Adat Hindu Bali di Kecamatan Kerambitan Kabupaten Tabanan - I Gede Komang Rahmadi; Benyamin Tunga (Penerbit Goodwood, 2022)
Purpose: The purpose of this research is to find out the perspective of Balinese Hindu law in interfaith marriages between Hinduism and Islam so that it can be declared legal and how the impact of inheritance law on intermarriage between Hindu and Islamic religions according to Balinese Hindu customary law. Method: The method used is an empirical juridical approach. This juridical approach emphasizes legislation and regulations relevant to this issue. While the empirical approach, emphasizing the problems studied based on the facts that develop in the research field. Result: Based on the results of the study, a conclusion can be drawn on the problem namely, According to the Balinese Hindu customary law intermarriage between Hindu and Islamic religions is invalid because besides being not justified in Customary Law, interfaith marriages conflict with existing national legal regulations, and also the Impact of the Inheritance Law on interfaith marriages between Hinduism and Islam according to the Balinese Hindu Customary Law is that the Inheritance Rights of the heirs become void, because the heirs are considered to have been ungodly towards their ancestors and religion.